Evaluating Patients With Impaired Renal Function During Drug Development: Highlights From the 2019 US FDA Pharmaceutical Science and Clinical Pharmacology Advisory Committee Meeting. Issue 2 (16th February 2021) - Sahre, Martina D.; Milligan, Lauren; Madabushi, Rajanikanth; Graham, Richard A.; Reynolds, Kellie S.; Terzic, Andre; Benjamin, Jessica; Burckart, Gilbert J.; Huang, Shiew‐Mei; Schuck, Robert; Thompson, Aliza M.; Zineh, Issam
Abstract : Patients with multiple chronic conditions, including more advanced chronic kidney disease (CKD), are often excluded from clinical trials, creating challenges in deriving appropriate dosing information and labeling. This article summarizes the May 7, 2019, US Food and Drug Administration Pharmaceutical Science and Clinical Pharmacology Advisory Committee Meeting, which solicited expert opinions on how to enroll patients with more advanced CKD into clinical trials as well as the assumptions behind and different approaches of exposure‐matching.